2018
DOI: 10.1021/jacs.8b10238
|View full text |Cite
|
Sign up to set email alerts
|

Radical Hydroarylation of Functionalized Olefins and Mechanistic Investigation of Photocatalytic Pyridyl Radical Reactions

Abstract: We report the photoredox alkylation of halopyridines using functionalized alkene and alkyne building blocks. Selective single-electron reduction of the halogenated pyridines provides the corresponding heteroaryl radicals, which undergo anti-Markovnikov addition to the alkene substrates. The system is shown to be mild and tolerant of a variety of alkene and alkyne subtypes. A combination of computational and experimental studies support a mechanism involving proton-coupled electron transfer followed by medium-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 82 publications
2
66
0
Order By: Relevance
“…This suggests that H‐bond interactions and/or a certain degree of protonation (or Lewis acid assistance) is essential for raising the reduction potential of these molecules into an accessible range . Whilst predicting the extent of imine protonation at the event of electron transfer is challenging, calculation of the reduction potentials for both the imine ( 1 a ) and lepidine species ( 2 a ), in both their neutral and protonated forms, provides an estimate of the operating window. As expected, protonation raises the reduction potentials (easier to reduce) for both 1 a and 2 a species into the operating range of the photocatalyst [Ir].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that H‐bond interactions and/or a certain degree of protonation (or Lewis acid assistance) is essential for raising the reduction potential of these molecules into an accessible range . Whilst predicting the extent of imine protonation at the event of electron transfer is challenging, calculation of the reduction potentials for both the imine ( 1 a ) and lepidine species ( 2 a ), in both their neutral and protonated forms, provides an estimate of the operating window. As expected, protonation raises the reduction potentials (easier to reduce) for both 1 a and 2 a species into the operating range of the photocatalyst [Ir].…”
Section: Resultsmentioning
confidence: 99%
“…The electrophilic sulfonyl radical 7 would subsequently undergo facile radical addition to alkene to generate the nucleophilic benzylic radical 9. At this stage, we envisioned that radical-radical coupling between the transient benzylic radical 9 and the persistent pyridyl radical anion 4 would forge β-sulfonyl pyridine 10 [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . Due to the acidity of the benzylic proton and the good leaving ability of sulfone, alkyl sulfone 10 would be expected to undergo E1 elimination with the assistant of base, furnishing the final branched alkenylpyridine product 11, as well as sulfinate 6 that could be recycled.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, radical-based chemistry provides an alternative platform to address this challenge. Particularly, the groups of MacMillan, Jui, and others [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] have successfully demonstrated that visible light photocatalyzed cross-couplings of pyridines to access to alkylated pyridines under mild conditions, by taking advantage of unique reactivity of open-shell pyridyl radical species (Fig. 1b).…”
mentioning
confidence: 99%
“…In 2018, Jui and co-workers developed a new catalytic system for the hydroarylation of nucleophilic functionalized olefins (Scheme 18). [45] This work was driven by the poor yield of the model reaction between 4-bromopyridine and vinyl acetate; significant amounts of oligomeric by-products were formed via pyridyl units coupling with multiple equivalents of vinyl acetate. To increase the rate of the HAT to the nucleophilic α-oxy radical intermediate, thus making radical addition more favourable than olefin incorporation, they attempted various electrophilic polarity-reversal catalysts.…”
Section: Reactions Of Haloazaarenesmentioning
confidence: 99%